Delayed Diagnosed of Relapse Malaria Vivax in Pregnancy: Good Outcome After Prompt Therapy - Stella Pangestika; Roy Boris; Revena Astanti Percunda; Ni Luh Putu Yunia Dewi; Asep Purnama (Riviera Publishing, 2026)
Malaria remains a major global health problem, particularly in endemic regions such as Indonesia, where pregnant women are highly vulnerable to infection and complications. Relapse Plasmodium vivax infection is increasingly recognized as a clinical challenge due to its dormant liver stage and potential for recurrent disease during pregnancy. This study aims to describe the clinical presentation, diagnostic approach, and management outcome of relapse vivax malaria in a third-trimester pregnant patient. A case report design was used based on clinical history, physical examination, laboratory findings, peripheral blood smear, and rapid diagnostic testing. The patient presented with fever, thrombocytopenia, and icteric sclera, and was confirmed positive for Plasmodium vivax with significant parasitemia and received dihydroartemisinin–piperaquine therapy with marked clinical improvement and platelet recovery. Findings emphasize the difficulty of differentiating malaria relapse from other hematologic conditions in pregnancy and the importance of early diagnosis in endemic areas. Early recognition and prompt treatment are essential to improving maternal and fetal outcomes in relapse vivax malaria during pregnancy. Future studies should focus on prevention of relapse, optimization of diagnostic algorithms, and evaluation of safe antimalarial strategies in pregnant populations in endemic regions. This will support better clinical decision-making and maternal health outcomes in practice